2019
DOI: 10.1097/bpo.0000000000001269
|View full text |Cite
|
Sign up to set email alerts
|

Unicortical Fixation is Sufficient for Surgical Treatment of Tibial Tubercle Avulsion Fractures in Children

Abstract: Background: Although open reduction and internal fixation are recommended for displaced tibial tubercle avulsion fractures in young athletes, whether to use unicortical or bicortical fixation is debatable. The purpose of this study is to compare the outcomes of unicortical versus bicortical fixation in a series of pediatric tibial tubercle avulsion fractures. Methods: We reviewed a consecutive series of patients with tibial tubercle fractures treated su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 8 publications
1
40
0
2
Order By: Relevance
“…Despite the force of the knee’s extensor mechanism transmitted to the tibial tubercle during knee motion, prior work has already demonstrated that unicortical screw fixation strategies—the method of fixation used in 91% of cases in our study—has equivalent outcomes to bicortical fixation. Our findings represent another departure from dogma, safely evolving the management of TTAFs 13. The equivalence of early ROM demonstrated in this study, regardless of fracture type or fixation strategy, suggests that there is no added benefit of immobilization from a fracture healing or long-term outcome standpoint.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Despite the force of the knee’s extensor mechanism transmitted to the tibial tubercle during knee motion, prior work has already demonstrated that unicortical screw fixation strategies—the method of fixation used in 91% of cases in our study—has equivalent outcomes to bicortical fixation. Our findings represent another departure from dogma, safely evolving the management of TTAFs 13. The equivalence of early ROM demonstrated in this study, regardless of fracture type or fixation strategy, suggests that there is no added benefit of immobilization from a fracture healing or long-term outcome standpoint.…”
Section: Discussionmentioning
confidence: 60%
“…Type IA, IB, and IIA fractures are typically treated nonoperatively, with immobilization in a long leg cast for 4 to 6 weeks 3,4,8,12. Open reduction and internal fixation with unicortical or bicortical screws is recommended for type IIB, IIA/B, IVA/B, and V fractures 1,3,12,13. However, nonoperative management and tension band wiring of type II and IV fractures with full recovery has also been reported 14,15…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two authors have reported that unicortical fixation provides sufficient metaphyseal stability compared with bicortical fixation. 14,15 In the current series, all patients underwent unicortical fixation with immobilization and with no loss of fixation or fracture displacement.…”
Section: Discussionmentioning
confidence: 95%
“…These features are consistent with previous reports outside of China. [10][11][12][13][14][15] Riccio et al 16 In children, obesity is thought to be a risk factor for the lower extremity fractures. 18 19 Sabhaney et al 20 showed that increased risk of fractures among normal-weight children compared with underweight children has been proven to be proportional to BMI.…”
Section: Discussionmentioning
confidence: 99%